1993
DOI: 10.1037/1040-3590.5.4.408
|View full text |Cite
|
Sign up to set email alerts
|

The Beck Anxiety Inventory: A psychometric analysis.

Abstract: This study sought to provide information on the Beck Anxiety Inventory (BAI) with respect to psychometric properties, gender differences, and relation to depression. A sample of 291 psychiatric patients completed the BAI, and a subsample of 251 completed the Beck Depression Inventory (BDI). The results from factor analyses demonstrated that the BAI has 2 factors, corresponding to cognitive and somatic symptoms. Although men and women did not differ in terms of factor structures, they did differ on mean levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
106
6
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(131 citation statements)
references
References 32 publications
13
106
6
2
Order By: Relevance
“…Beck and colleagues (Beck et al 1988) reported high internal consistency (α=0.92), testretest reliability (r=0.75), and good discrimination of anxiety disorders from nonanxiety disorders over 1 week. The psychometric properties of the BAI have been further supported in clinical and nonclinical samples (Clark et al 1994;Hewitt and Norton 1993;Steer et al 1993). …”
Section: Methodsmentioning
confidence: 88%
“…Beck and colleagues (Beck et al 1988) reported high internal consistency (α=0.92), testretest reliability (r=0.75), and good discrimination of anxiety disorders from nonanxiety disorders over 1 week. The psychometric properties of the BAI have been further supported in clinical and nonclinical samples (Clark et al 1994;Hewitt and Norton 1993;Steer et al 1993). …”
Section: Methodsmentioning
confidence: 88%
“…The questionnaires included a measure of personality e the Zuckerman-Kuhlman Personality Questionnaire (five factors: sociability, neuroticism, activity, impulsive sensation seeking, aggression; Zuckerman et al, 1993); a measure of emotion regulation e the Emotion Regulation Questionnaire (two factors: cognitive reappraisal and emotional suppression; Gross and John, 2003); baseline measures of depression and anxiety levels e Beck's Depression Inventory (Beck and Steer, 1984;Beck et al, 1988b) and Beck's Anxiety Inventory (Beck et al, 1988a;Hewitt and Norton, 1993); an inventory of health risk behaviors including questions from the alcohol use disorders identification test (Saunders et al, 1993), the Centers for Disease Control and Prevention's youth risk behavior survey regarding tobacco use (Center for Disease Control and Prevention, 2009), and the Driving Behavior Questionnaire (Parker et al, 1995) as well as a question regarding Army Substance Abuse Program (ASAP) referral; a measure of risk propensity e the Evaluation of Risks Questionnaire (EVAR-English version; three factors: need-for-control, selfconfidence, risk/thrill seeking; Sicard et al, 2001;Killgore et al, 2006); and a measure of perceived invincibility, the Invincibility Belief Index (IBI; total invincibility belief score and three factors: adroitness, impunity, boldness; Killgore et al, 2010). Additionally, participants completed a measure of behavioral risk-taking e the Balloon Analog Risk Task (Lejuez et al, 2002); and a behavioral decision making task incorporating uncertainty, reward, and punishment ethe Iowa Gambling Task (Bechara et al, 1997(Bechara et al, , 2001(Bechara et al, , 2000.…”
Section: Surveys and Outcome Variablesmentioning
confidence: 99%
“…This measure exhibits adequate levels of reliability to assess pain in non-cancer samples, with coefficient alphas of .70 and above, also evidences good concurrent validity with other generic pain measures, and has been shown to be sensitive to changes in pain status over time (Keller et al, 2004). Norton, 1993;Steer, Clark, Beck & Ranieri, 1995). Factor analysis of the BAI and BDI yielded a first-order factor labeled anxiety that had salient loadings for all 21 items on the BAI, but only one item on the BDI.…”
Section: Beck Depression Inventory (Bdi-ii)-because Depression Is Thementioning
confidence: 99%
“…Beck Anxiety Inventory (BAI)-Anxiety symptoms were measured with the BAI, a 21-item self-report measure with established and replicated construct validity (Hewitt & Norton, 1993;Steer, Clark, Beck & Ranieri, 1995). Factor analysis of the BAI and BDI yielded a first-order factor labeled anxiety that had salient loadings for all 21 items on the BAI, but only one item on the BDI.…”
Section: Beck Depression Inventory (Bdi-ii)-because Depression Is Thementioning
confidence: 99%